Coxiella burnetii replicates in Galleria mellonella hemocytes and transcriptome mapping reveals in vivo regulated genes. Issue 1 (1st January 2020) - Kovacs-Simon, Andrea; Metters, Georgie; Norville, Isobel; Hemsley, Claudia; Titball, Richard W.
ABSTRACT: Larvae of the greater wax moth ( Galleria mellonella) are susceptible to infection with C. burnetii, an obligate intracellular bacterial pathogen. We show that bacteria are found in hemocytes after infection, and occupy vacuoles which are morphologically similar to Coxiella -containing vacuoles seen in infected mammalian phagocytes. We characterized the infection by transcriptome profiling of bacteria isolated from the hemocytes of infected larvae and identified 46 highly upregulated genes. The encoded proteins are predicted to be involved in translation, LPS biosynthesis, biotin synthesis, scavenging of reactive oxygen species, and included a T4SS effector and 30 hypothetical proteins. Some of these genes had previously been shown to be upregulated in buffalo green monkey (BGM) cells or in mice, whilst others appear to be regulated in a host-specific manner. Altogether, our results demonstrate the value of the G. mellonella model to study intracellular growth and identify potential virulence factors of C. burnetii .